2015
DOI: 10.1371/journal.pone.0133873
|View full text |Cite
|
Sign up to set email alerts
|

Cis-Antisense Transcription Gives Rise to Tunable Genetic Switch Behavior: A Mathematical Modeling Approach

Abstract: Antisense transcription has been extensively recognized as a regulatory mechanism for gene expression across all kingdoms of life. Despite the broad importance and extensive experimental determination of cis-antisense transcription, relatively little is known about its role in controlling cellular switching responses. Growing evidence suggests the presence of non-coding cis-antisense RNAs that regulate gene expression via antisense interaction. Recent studies also indicate the role of transcriptional interfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 94 publications
2
39
0
Order By: Relevance
“…HIF1A‐AS2, the antisense RNA under study, represents an unique example given its overlapping yet opposite genomic orientation relative to HIF‐1A, which give rises to a convergent transcription, and also its strong and direct activation by HIF‐1A . In line with the notion that antisense transcripts can regulate their neighboring genes in cis , a hypoxia‐associated transcriptome profiling reported by Choudhry et al showed that the expression of the sense–antisense gene pair exhibits a converse pattern under low oxygen stress—HIF1A‐AS2 is expectedly induced whereas HIF‐1A mRNA is reduced. This is consistent with our gene expression analysis (Fig A) and, together with our functional characterization of HIF1A‐AS2, strongly supportive of a transcription‐based negative‐feedback regulation.…”
Section: Discussionmentioning
confidence: 77%
“…HIF1A‐AS2, the antisense RNA under study, represents an unique example given its overlapping yet opposite genomic orientation relative to HIF‐1A, which give rises to a convergent transcription, and also its strong and direct activation by HIF‐1A . In line with the notion that antisense transcripts can regulate their neighboring genes in cis , a hypoxia‐associated transcriptome profiling reported by Choudhry et al showed that the expression of the sense–antisense gene pair exhibits a converse pattern under low oxygen stress—HIF1A‐AS2 is expectedly induced whereas HIF‐1A mRNA is reduced. This is consistent with our gene expression analysis (Fig A) and, together with our functional characterization of HIF1A‐AS2, strongly supportive of a transcription‐based negative‐feedback regulation.…”
Section: Discussionmentioning
confidence: 77%
“…A decrease in maternal expression of Commd1 also occurred concomitantly with the activation of maternal Zrsr1, which strongly suggests that the predominant maternal expression of Commd1 results from Zrsr1-mediated reduction in the expression of Commd1 from the paternal allele. Studies on genetic organization in genomes have identified overlapping and antisense-oriented genes, and the mutual cis-acting effect on their expression, which is termed transcriptional interference (Bordoy & Chatterjee, 2015). The active transcription of Zrsr1 within Commd1 may cause collisions between the opposing Zrsr1 and Commd1 elongation complexes, which would result in the reduction in their expression.…”
Section: Discussionmentioning
confidence: 99%
“…There are two known modes of transcriptional regulation by antisense transcription: antisense RNA (asRNA) regulation, where sense and antisense RNAs hybridize to promote RNAsemediated degradation or block the ribosome binding site to prevent its translation (8)(9)(10), and collisions of the transcriptional machinery originated from sense and antisense promoters, termed transcriptional interference (TI) (8,(10)(11)(12). Three primary modes of TI-RNA Polymerase (RNAP) collisions, sitting duck, and promoter occlusion-have been proposed (11) and parsed through experiments (13) and mathematical modeling (9,14). Direct contact of bacterial RNAPs has not been observed during head-on RNAP collisions (15), and it is generally understood that interference of one RNAP on another may be mediated through DNA supercoiling (16,17) rather than due to direct collisions of transcriptional machinery.…”
Section: Introductionmentioning
confidence: 99%